METODE PROFILE MATCHING SEBAGAI PENUNJANG KEPUTUSAN PEMBERIAN KREDIT PADA CV BUANA MOTOR - Hendry; Erlin Elisa (LPPM Universitas Putera Batam, 2025)
The credit approval process at CV. Buana Motor has traditionally been carried out manually and subjectively, which can lead to inaccuracies in decision-making. To address this issue, a decision support system is needed to assist in assessing the eligibility of prospective debtors more objectively. This study aims to apply the profile matching method as a tool to determine credit eligibility based on several predefined criteria, including income, installment amount, installment duration, type of employment, home ownership status, and length of residence. The first three criteria are classified as core factors, while the remaining three are considered secondary factors. This study uses data from 340 customers as samples. The results show that 273 customers (approximately 80.29%) were classified as eligible for credit, while 67 customers (19.71%) were deemed ineligible. These findings indicate that the profile matching method can provide systematic and objective assessment results and effectively support the credit decision-making process at CV. Buana Motor.